PENGARUH PEMAHAMAN WAJIB PAJAK DAN MANFAAT PAJAK RESTORAN TERHADAP KEMAUAN WAJIB PAJAK MEMBAYAR PAJAK (STUDI KASUS PADA USAHA RESTORAN DI KABUPATEN MINAHASA DAN KOTA TOMOHON) - Wowor, Pingkan Elni; Sondakh, Jullie J.; Pinatik, Sherly (ACCOUNTABILITY, 2015)
Tax is one of the sources of government revenue that can be relied upon, in this case, especially in the financing of local government. But in the collection muidah it would not, because in addition demanded the active role of taxation officers are also required the willingness of the taxpayer itself in paying taxes. Lack of willingness of taxpayers to pay their taxes can not be separated from the lack of knowledge on taxation, as well as the lack of such benefits in the eyes of society. Many still regard as a tax expenditure in vain. this is one of the factors that hinder the taxpayer in carrying out their tax obligations. Purpose of this study was to determine the understanding of taxpayers and tax benefits restaurant on the willingness of taxpayers to pay taxes in Minahasa district and in the town of Tomohon. Methods of analysis used in this study is the method of multiple linear regression analysis.Testing hypotheses used in this study is the F test and T test F test is to determine the effect of independent variables on the dependent variable simultaneously, whether significant effect or not, and T test to determine the effect of independent variables on the dependent variable partially, whether the effect significant or not.Based on the results of research conducted shows that in Minahasa, simultaneously understanding of the taxpayer and the tax benefit Restaurant significant effect on the willingness of taxpayers to pay taxes, and partial understanding of the taxpayer does not affect the willingness of taxpayers taxpayer, while the effect on the restaurant tax benefits the willingness of taxpayers taxpayer. In Tomohon, simultaneously understanding of the taxpayer and the tax benefit Restaurant significant effect on the willingness of taxpayers to pay taxes, and partial understanding of the taxpayer and the tax benefits of the restaurant affect the willingness of taxpayers taxpayer. This is evidenced by testing of the data obtained in this study.